Evaluación del desempeño de nanopartículas de magnetita en la remoción de cobre respecto al método convencional de precipitación alcalina para el tratamiento de aguas de producción del campo “B” a nivel de laboratorio con fines de reinyección (2021)
In Colombia for the year 2020, it was estimated that the water-oil production ratio (RAP) reached 16 barrels of water for every barrel of oil and worldwide it varied between 10 and 14 for mature fields. These waters are characterized by the negative effects they can have on the environment; For this reason, they are currently considered one of the largest pollutants in the world, since for their reuse they must be previously treated. Among the most common uses that are given to treated water, reinjection stands out, for which it is necessary to remove heavy metals such as copper, because in high concentrations it can alkalize and degrade the formation, in addition to forming precipitation, scale and corrosion in pipes.